International Encyclopedia of Geography 2017
DOI: 10.1002/9781118786352.wbieg0605
|View full text |Cite
|
Sign up to set email alerts
|

Geovisualization of Social Media

Abstract: The proliferation of social media over the last decade is presenting substantial computational challenges associated with the management, processing, analysis, and visualization of the corresponding massive volumes of data. Furthermore, this new form of information also imposes newfound challenges upon the geographical community due to the unique nature of its content, as analyzing such data calls for a hybrid mix of spatial and social analysis. The spatial content of social media comprises primarily coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…These patterns of geolocation are consistent with figures reported from other analyses. More specifically, the precisely geolocated tweets represented 0.94% (toponym reference: 52.60%) of the total number of tweets, and broader studies have reported such precisely geolocated tweets to amount to between 0.5% and 3% of the overall traffic with toponym references typically ranging from 40-70% [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…These patterns of geolocation are consistent with figures reported from other analyses. More specifically, the precisely geolocated tweets represented 0.94% (toponym reference: 52.60%) of the total number of tweets, and broader studies have reported such precisely geolocated tweets to amount to between 0.5% and 3% of the overall traffic with toponym references typically ranging from 40-70% [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies using geocomputation and geovisualisation have also been performed in the domains of human activity pattern analysis (Mei-Po Kwan, 2004), sediment contamination assessment (Forsythe et al, 2016), and social media analysis (Croitoru et al, 2017).…”
Section: Related Workmentioning
confidence: 99%
“…Social network analysis and geospatial analysis are two promising computational methods for studying the structures of social and physical spaces within which humans live and interact, especially with the advent of crowdsourced information and the rise of social media [142,143]. Social network analysts see the social world as structured by a web of connected agents tied together by specific relationships [144].…”
Section: Social Network and Geospatial Analysismentioning
confidence: 99%